Meta-analysis: Bilateral and Unilateral Cerebral Perfusion in Type A Dissection - Naito, Noritsugu; Takagi, Hisato (The Thoracic and Cardiovascular Surgeon, 2024)
Background This meta-analysis compared the outcomes of bilateral cerebral perfusion (BCP) and unilateral cerebral perfusion (UCP) in aortic surgery for acute type A aortic dissection.Methods A systematic literature search identified 12 studies involving 4,547 patients. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated to analyze perioperative characteristics, short-term mortality rates, and postoperative neurological complications.Results No significant differences were found between the BCP and UCP groups in terms of cardiopulmonary bypass time, aortic cross clamp time, lowest body temperature, and lower body circulatory arrest time. Short-term mortality rates (OR [95% CI] = 0.87 [0.64–1.19], p = 0.40) and permanent neurological deficits (OR [95% CI] = 1.01 [0.69–1.47], p = 0.96) were comparable between the groups. However, subgroup analysis of studies exclusively involving total arch replacement showed a lower short-term mortality rate (OR [95% CI] = 0.42 [0.28–0.63], p < 0.01) and permanent neurological deficits (OR [95% CI] = 0.53 [0.30–0.92], p = 0.03) in the BCP group. The BCP group also had a lower rate of temporary neurological deficits (OR [95% CI] = 0.70 [0.53–0.93], p = 0.01), particularly in studies exclusively involving total arch replacement (OR [95% CI] = 0.58 [0.40–0.85], p < 0.01).Conclusion This meta-analysis suggests that BCP and UCP yield comparable outcomes. However, BCP may be associated with lower short-term mortality rates and reduced incidence of neurological complications, particularly in cases requiring total arch replacement. BCP should be considered as a preferred cerebral perfusion in specific patient populations.
Keywords: cerebral perfusion; acute type A aortic dissection; meta-analysis